2019
DOI: 10.1007/s40093-019-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bambara groundnut (Vigna subterranea L. Verdc.) with rice husk biochar and Christmas Island Rock Phosphate application

Abstract: Purpose Biochar application could be a sustainable way to enhance the nitrogen fixation in Bambara groundnut and other legumes. The research was conducted to study the effect of rice husk biochar and the Christmas Island Rock Phosphate application on the performance of Bambara groundnut in the study area. Methods Two levels of rice husk biochar (0 and 10 t/ha) and four levels of Christmas Island Rock Phosphate (0, 20, 40 and 60 kg P 2 O 5 /ha) were factorially combined to make a total of eight treatment combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Research has revealed that Bambara groundnut production can differ from 380 to 1000 kg ha −1 based on the genotype or landrace used [8]. Similarly, in a study conducted by [9] to study the influence of nitrogen fixation and the N-balance of its landraces cultivated on Malaysia's acidic tropical soils, they observed 374-896 kg ha−1 in pod yield. The crop produces higher grain yields with a projected world production of 331,000 tons.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that Bambara groundnut production can differ from 380 to 1000 kg ha −1 based on the genotype or landrace used [8]. Similarly, in a study conducted by [9] to study the influence of nitrogen fixation and the N-balance of its landraces cultivated on Malaysia's acidic tropical soils, they observed 374-896 kg ha−1 in pod yield. The crop produces higher grain yields with a projected world production of 331,000 tons.…”
Section: Introductionmentioning
confidence: 99%